Canonical form of polynomial matrices with all identical elementary divisors - Shavarovskyy, B. Z. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
The problem of reducing polynomial matrices to the canonical form by using semiscalar equivalent transformations is studied. A class of polynomial matrices is singled out, for which the canonical form with respect to semiscalar equivalence is indicated. This form enables one to solve the classification problem for collections of matrices over a field up to similarity.